Antigenic differences between wildtype measles viruses and vaccine viruses in Indonesia - Made Setiawan; Agus Sjahrurachman; Fera Ibrahim; Agus Suwandono (Indonesian Pediatric Society, 2008)
Background Measles virus has a single, negative strand RNAgenome which codes 6 structural proteins: N, F, P M, H and L.Currently there are several variances in the nucleotide sequencesof N, F, M and H genes across wild type measles viruses, hencemeasles viruses can be categorized into clades and genotypes. Theantigenicity of the previous genotype of measles is different fromthe current genotype.Objective To determine the antigenic differences between wildtype measles virus and measles vaccine virus.Methods Analysis of the antigenic differences between wild typevirus (G2, G3 and D9) and vaccine virus (CAM-70 and Schwarz)was performed by immunizing mice with the respective viruses.The serum was then tested with micro-cross-neutralizationtechnique using the G2, G3, D9 and CAM-70 virus. Tests withcross ELISA examination technique were also performed usingthe same set of virus.Results Analysis of the cross neutralization test and cross ELISAshowed that the highest antigenicity reaction was found betweenwild type virus with antibody against wild type virus, while thelowest reaction was between wild type virus with antibody againstCAM-70.Conclusions We conclude that the antigenicity of antigenic proteinfrom wild type virus is higher than antigenicity of vaccine virusprotein. In addition, it was found that the antigenicity of proteinsfrom Schwarz vaccine virus was higher than proteins CAM-70vaccine virus.